Recognizing Racism in Medicine: A Student-Organized and Community-Engaged Health Professional Conference - Ademide A. Adelekun; Julia Carney; Whitney U. Orji; Emily Rider-Longmaid; Daniel C. Stokes; Stephanie Teeple; Jaya Aysola (Mary Ann Liebert, 2019)
Purpose: This piece details the evaluation and implementation of a student-led educational intervention designed to train health professionals on the impact of racism in health care and provide tools to mitigate it. In addition, this conference, cosponsored by medical, nursing, and social work training programs, facilitates development of networks of providers with the knowledge and skills to recognize and address racism in health care. Methods: The conference included 2 keynote speakers, an interprofessional panel, and 15 workshops. Participants (n=220) were asked to complete a survey assessing perceptions of conference content and impact. We compared responses pre- and postconference using Wilcoxon signed-rank tests. Results: Of the survey respondents (n=44), 45.5% were medical students, 13.6% nursing students, and 9% social work students; 65.9% self-identified as a race/ethnicity other than non-Hispanic white; and 63.6% self-identified as female. We found that 47.7% respondents reported they were more comfortable discussing how racism affects health (p<0.001), 36.4% had better understanding of the impact of racism on an individual's health (p<0.001), and 54.5% felt more connected to other health professionals working to recognize and address racism in medicine (p<0.001). Conclusion: These findings suggest that a student-organized conference could potentially be an effective strategy in addressing a critical gap in racism training for health care professionals.